Medication Adherence of Tamoxifen to Breast Cancer Patients and the Affecting’s Factors in Dharmais Cancer Hospital Jakarta - Via Dolorosa Halilintar; Mardiati Nadjib; Lucia Rizka Andalusia (Universitas Muhammadiyah Yogyakarta, 2020)
Several previous studies show that adherence to hormonal therapy increases the survival rate in Breast Cancer (BC) with ER+ or PR+. Tamoxifen is one of oral chemotherapy which is the most used hormonal therapy in breast cancer treatment regimens. The focus of the study was to determine the level of adherence and factors influencing the adherence of the treatment of BC patients undergoing hormonal therapy with Tamoxifen in patients at Dharmais Cancer Hospital in the year 2018. The study is an observational study with a cross-sectional design. The study was followed by 109 respondents. Medication adherence levels assessed via questionnaire modified MARS-5. Sociodemographic and clinical characteristics obtained from interviews using structured questionnaires. Medication adherence’s level of Tamoxifen was 90.9% with the proportion of adhering patients was 75.2% (82 of 109 patients). Multivariate analysis showed that the age of respondents, level of education, level of knowledge is the most influential factor and determine the level of treatment adherence. Education level is the variable that has the greatest effect on medication adherence. Through this study, it is recommended to pay more attention to patients with specific characteristics such as patients with low education and or low income.